PENGARUH SIMPANAN MASYARAKAT DAN UKURAN PERUSAHAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Maryana Maryana; nurlina nurlina (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2019)
The purpose of this study was to examine the influence of public deposits and the size of the company to profitability in banking companies listed in Indonesia stock exchange. The data used in this research is secondary data that is annual report of banking companies 2009-2015 period. The source of the data derived from five banking companies listed in Indonesia stock exchange. Data processing was performed using SPSS with multiple linear regresion. The results showed that: Saves society negatively affects the profitability of the banking company listed on the Indonesia stock exchange. Size companies positive effect on the profitability of the banking company listed on the Indonesia stock exchange. Simultaneously, public deposits and the size of the company's positive effect on the profitability of the banking company listed on the Indonesia stock exchange. Public deposits and the size of the firm has a weak correlation with the profitability of the banking company listed on the Indonesia stock exchange. Public deposits and the size of the companies have the leverage to explain the profitability of the banking company listed on the Indonesia stock exchange amounted to 61.1%, while the remaining 38.9% is influenced by other variables outside this research model. Keywords : Public Deposits, Size of the Company, Profitability